Developing a legal and institutional framework for witness protection in Nigeria: reflections from international perspectives - Oyakhire, Suzzie Onyeka (Department of Public Law, 2020)
'Witness protection' has been introduced in the criminal justice systems of several states worldwide as a recognised tool for facilitating the cooperation of witnesses and ensuring that concerns about their safety are not ignored. Although not a new phenomenon, witness protection praxis continues to evolve and remains largely undeveloped in many states. In Nigeria, the relevance of witness protection as a critical aspect of criminal justice administration is increasingly becoming evident. As an area of enquiry, scholarly literature on witness protection is descriptive, locally focused, and lacking in conceptual clarification. Recent developments in Nigeria highlight the need for the clarification of legal and conceptual issues within the existing legal framework for protecting witnesses. Using the Nigerian case study, this thesis illustrates the obscurities inherent in the concept of witness protection. These are highlighted around five critical areas: the definition of witness protection; the scope of beneficiaries requiring protection; the nature of crimes necessitating protection; the nature of protective measures; and the administrative control of witness protection. The thesis explores the concept of witness protection, which is still at an early developmental stage in Nigeria. In the absence of a clear legal jurisprudence, the thesis pieces together the practice of witness protection in Nigeria and embarks on a conceptual and legal clarification of issues important to developing a witness protection framework. To achieve this, the thesis draws from international debates, legal developments and institutional practices from other jurisdictions as a basis for improving Nigerian efforts in witness protection and for making normative proposals to that effect. The thesis utilises two distinct perspectives: the criminal justice and the human rights perspectives as heuristic tools for analysing the concept of witness protection and to separate the disparate influences that shape how it is construed. A combination of desktop research by way of doctrinal research and empirical research was adopted. In pursuit of a more detailed understanding of contemporary developments relating to witness protection in Nigeria, field research was undertaken. This comprised qualitative research using semi-structured interviews of a specifically selected sample of criminal justice experts and practitioners with knowledge about witness protection in Nigeria. The semi-structured interviews justify the assumptions that there is a need to examine and clarify the scope of witness protection and what it depicts. The thesis finds that the concept and practice of witness protection evolved within specific parameters and its definitions are determined within these limits. It advances the existing witness protection conversations by offering an analytical basis for discussing witness protection and proposes organising principles for delineating the scope of witness protection. The clarifications made in the analysis within this thesis are utilised in making normative proposals and policy recommendations for developing a legal framework for witness protection in Nigeria. The thesis recommends a formal witness protection framework, through the enactment of comprehensive witness protection legislation that clearly defines the objectives of witness protection, the scope of beneficiaries, the scope of crimes necessitating protection, the type of protective measures and guidelines for assigning these measures, clear eligibility criteria and which establishes an independent witness protection agency to administer witness protection in Nigeria.